Asuhan Keperawatan Pada Pasien Stroke Non Hemoragic Dengan Intervensi Penerapan Range Of Motion (R.O.M) Pasif Untuk Meningkatkan Kekuatan Tonus Otot Di RSUD Kabupaten Tangerang - Johanes Parasian; Meynur Rohmah; Dwi Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Stroke is a manifestation of systemic disease in the elderly in the form of circulatory disorders to the brain that cause neurologic deficits, it is necessary to carry out appropriate nursing interventions or action plans such as joint strengthening exercises / Range Of Motion (ROM) techniques. Objective: To identify research articles about the duration of administration and the effects before and after ROM nursing actions were given on muscle strength, walking balance and joint span in non-hemorrhagic stroke patients with impaired physical mobility. Research Methods: This research is a literature review study by searching for articles through Google Scholar. Research results: The results of a literature review on 4 research articles on ROM nursing actions in stroke, there is an effect before and after being given ROM actions on stroke by increasing muscle strength, walking balance and joint range of motion. Conclusion: The results in 4 research articles on ROM nursing actions in stroke related to the time of giving ROM actions with different durations of administration and there was an effect before and after being given ROM actions on stroke. Suggestion: For stroke patients, it can be used as a reference for information in healing stroke. Nurses need to routinely apply ROM in the hospital to stroke and post-stroke patients to reduce severe paralysis problems.